FFECTIVE RETRIEVAL OF RELEVANT WEB DOCUMENTS: A QUERY EXPANSION APPROACH USING FORMAL CONCEPT ANALYSIS - Umar, Abdullahi Bn (FUDMA JOURNAL OF SCIENCES, 2025)
In information retrieval, vocabulary mismatch between the search vocabulary and documents vocabulary has been a common challenge for web users, hindering information access and retrieval. This issue is often attributed to the ambiguous representation of user information needs as queries, leading to the retrieval of many irrelevant documents, particularly for non-skilled web users. This paper aims to improve user query representation for effective retrieval of relevant documents from the web. To achieve this, a query expansion strategy was employed to identify terms with similar meanings to the user’s initial query term. The similarities between the expanded terms and the initial user query term were determined by calculating the cosine angle between the vector resenting document vocabulary and the vector representing query term. Thereafter, Formal Concept Analysis (FCA) was employed to analyze and present the results. Findings from the analysis revealed that concatenating similar terms with the initial user query terms resulted in a 0.16% improvement, as evident in the retrieval precision of 0.64% with the initial query and 0.80% with the expanded query terms.